A fundamental role of the solvent polarity and remote substitution of the 2-(4-R-phenyl)-1H-imidazo[4, 5-f][1, 10]phenanthroline framework in controlling the ground- and excited-state properties of Re(i) chromophores [ReCl(CO)3(R-C6H4-imphen)]. Issue 38 (7th September 2022) - Szłapa-Kula, Agata; Palion-Gazda, Joanna; Ledwon, Przemyslaw; Erfurt, Karol; Machura, Barbara
Abstract : The ground- and excited-state properties of a new series of Re(i ) carbonyl chromophores with the 1 H -imidazo[4, 5- f ][1, 10]phenanthroline ligand functionalized with electron-donating amine groups were thoroughly investigated. Abstract : A series of Re(i ) carbonyl complexes with the 1 H -imidazo[4, 5- f ][1, 10]phenanthroline (imphen) ligand functionalized with electron-donating amine groups attached to the imidazole ring via phenylene linkages were designed to investigate the impact of remote amine substituents on the ground- and excited-state properties of [ReCl(CO)3 (R-C6 H4 -imphen)]. The complexes [ReCl(CO)3 (R-C6 H4 -imphen)] belong to the family of [ReCl(CO)3 (diimine)] systems, but contrary to strongly related phenanthroline Re(i ) carbonyl complexes with a rich history in coordination chemistry, they are really sparse. The effects of electron-rich N-donor groups in [ReCl(CO)3 (R-C6 H4 -imphen)] were fully studied with the use of cyclic voltammetry, absorbance and emission spectroscopy, and transient absorption spectroscopy, and they were simulated by density functional theory. The attachment of electron-rich amine groups to C6 H5 -imphen resulted in a decrease in oxidation potentials and a noticeable bathochromic shift of the longest absorption wavelength of [ReCl(CO)3 (R-C6 H4 -imphen)] compared with the parent compound [ReCl(CO)3 (C6 H5 -imphen)] due to a significant destabilization of the HOMO energy level. Regarding the excited-state properties, the triplet emission red-shift of [ReCl(CO)3 (R-C6 H4 -imphen)] induced by appended electron-rich N-donor groups was accompanied by a significant increase in excited state lifetimes, up to a 12-fold enhancement compared with the parent chromophore. The lifetime prolongation of [ReCl(CO)3 (R-C6 H4 -imphen)] bearing amine substituents was rationalized by the population of the ligand-localized triplet state, while the solvent-dependent photoluminescence characteristics of [ReCl(CO)3 (R-C6 H4 -imphen)] were correlated with strong hydrogen bonding interactions between the acidic imidazole NH proton and highly polar solvents. The present findings are of high importance for understanding and controlling the excited-state nature of transition metal complexes.